IMPROVING STUDENTS' VOCABULARY MASTERY USING CROSSWORD PUZZLE - Vina Novita Tambaritji; Nai Supartini Atmawidjaja (PROJECT (Professional Journal of English Education), 2020)
This study aims to determine the increase in students' mastery of English vocabulary using crosswords and to find out what are the effects of using crosswords in the learning process. This research uses classroom action research methods. Researchers conducted research in one of the junior high schools in Cimahi and the subjects in this study consisted of 34 students. For data collection researchers used observation, interviews and tests, to find out whether there was progress from students in improving their mastery of English vocabulary. This research was carried out in two cycles. In the first cycle the average value of students 58.97 and categorized as still very low or bad. Then the researchers proceed to the second cycle by using the steps in classroom action research and the researcher is more focused on attracting students' attention to focus on learning and explaining the instructions for working on crosswords. Therefore in the second cycle, the average value of students increased to 76.02 and the category is good. This shows that there is an increase in the mastery of English vocabulary after implementing crossword puzzle games in the learning process in the classroom. Keywords:  Improving, Vocabulary mastery, Crossword puzzle